2016
DOI: 10.1515/ijme-2016-0029
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Service Quality and Customer Loyalty: The Mediating Effect of Passenger Satisfaction in the Nigerian Airline Industry

Abstract: The long-term survival and competiveness of the airline business is strongly connected to the quality of service offered by airline operators and their ability to satisfy and build long-term relationships with customers. This study investigates the relationship among service quality, customer satisfaction and loyalty in the Nigerian airline industry. The cross-sectional survey research design was chosen in order to collect the primary data, using a structured questionnaire. Convenience sampling was adopted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 55 publications
2
21
1
3
Order By: Relevance
“…In the literature of marketing, the relationship between perceived quality and customer satisfaction has been a controversial issue (Rahim, 2016). Perceived service quality is suggested to be an antecedent of customer satisfaction in some previous studies (Bitner & Hubbert, 1994;Ravald & Gronroos, 1996).…”
Section: Overall Perceived Service Quality Satisfaction and Online Rmentioning
confidence: 99%
“…In the literature of marketing, the relationship between perceived quality and customer satisfaction has been a controversial issue (Rahim, 2016). Perceived service quality is suggested to be an antecedent of customer satisfaction in some previous studies (Bitner & Hubbert, 1994;Ravald & Gronroos, 1996).…”
Section: Overall Perceived Service Quality Satisfaction and Online Rmentioning
confidence: 99%
“…Customer satisfaction has become a fundamental goal of all business organisations; this position is derived from long held conviction that for a firm to be profitable, it must satisfy customers (Shin and Elliott, 2001;Ranaweera and Prabhu, 2003). Generally, academics and business practitioners have long admitted that customer satisfaction is one of the highest priorities of business organizations and research have also shown that customer satisfaction is a key determinant in maintaining and sustaining business relationship (Oliver, 1997;Ahmad, 2007;Rahim, 2016b). Essentially, customer satisfaction is influenced by overall quality/price expectations (Anderson, 1994), firm's image (Aga and Okan, 2007), and persons' desires (Spreng, MacKenzie and Olshavsky, 1996).…”
Section: Determinants Of Customer Satisfactionmentioning
confidence: 99%
“…It was cited by Fishbein and Azjen [10] as the single most accurate predictor of actual purchase behavior. This assertion was empirically tested and supported by Tellis [40] and Rahim [41] empirically tested and confirmed this in a study conducted on the consumer durable goods category. In the context of the current research, one could view viral marketing as a service offered by firms to potential customers.…”
Section: Purchase Intentionmentioning
confidence: 62%
“…Satisfaction is essentially the difference between expected and actual levels of performance by a product or service [33,41,42]. Owing to the increased realization that retention is an easier way to increase profits than the acquisition of new customers, satisfaction has gained increasing importance in the marketing literature [43,44,45].…”
Section: Purchase Intentionmentioning
confidence: 99%